2013
DOI: 10.1021/jp402331y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Ionic Liquids and Acetone: Thermodynamic Properties, Quantum-Chemical Calculations, and NMR Analysis

Abstract: The interactions between ionic liquids (ILs) and acetone have been studied to obtain a further understanding of the behavior of their mixtures, which generally give place to an exothermic process, mutual miscibility, and negative deviation of Raoult's law. COSMO-RS was used as a suitable computational method to systematically analyze the excess enthalpy of IL-acetone systems (>300), in terms of the intermolecular interactions contributing to the mixture behavior. Spectroscopic and COSMO-RS results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 66 publications
1
50
0
4
Order By: Relevance
“…The activity coefficients at 300, 400 and 500 K of the [Ch]Cl(1)þIC(2) systems were estimated by COSMO-RS and this information used to assess the ideality of the solutions. Before the estimations, all the IC structures were optimized [29]. The ions of each compound were optimized simultaneously as an ion pair.…”
Section: Assessment Of the Systems Idealitymentioning
confidence: 99%
See 1 more Smart Citation
“…The activity coefficients at 300, 400 and 500 K of the [Ch]Cl(1)þIC(2) systems were estimated by COSMO-RS and this information used to assess the ideality of the solutions. Before the estimations, all the IC structures were optimized [29]. The ions of each compound were optimized simultaneously as an ion pair.…”
Section: Assessment Of the Systems Idealitymentioning
confidence: 99%
“…The ions of each compound were optimized simultaneously as an ion pair. On a second step, the COSMO file of each structure was generated by Gaussian, computing the ideal screening charges on the molecular surface at the BVP86/TZVP/DGA level [29].…”
Section: Assessment Of the Systems Idealitymentioning
confidence: 99%
“…Regarding 1-alkyl-3-methyimidazolium-based ILs, there are three main binding sites in the imidazolium ion capable of participating as hydrogen bond donors, and these are at positions H-( 4 C), H-( 5 C), and H-( 2 C). Indeed, it was shown that the IL anion prefers to bind to the proton at the ( 2 C) position, the latter being the most acidic amongst the others [45][46][47], and that the introduction of a solute/solvent to the IL leads to a competition for the active sites of both ions, the outcome of which strongly depends on the differences between the acidic/basic properties of the participants [44][45][46][47][48][49][50][51][52]. In other words, solutes with pronounced acidic properties will compete with the imidazolium ion to form H-bonds with Cl − , whereas those with basic properties will compete with the chloride anion for the acidic sites of the cation.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the binding energy between water (or ethanol) and the entrainers, all optimized geometries were obtained by using the Gaussian 03 software package 50 at the M05-2X/ 6-31111G(d,p) level with the keyword "int 5 ultrafine," which has been previously used for studying the interactions between ILs and polar organic molecules. 51,52 The M05-2X functional is one of the newest DFT methods and is assumed to correctly reproduce weak interactions. 53 To obtain the most favorable clusters (composed of IL ions, KAc, water, and ethanol), harmonic frequency analysis calculations were performed to verify the optimized geometries to obtain the lowest energy points (no imaginary frequency) rather than local minima.…”
Section: Computational Details Quantum Chemical Calculationsmentioning
confidence: 99%